Unraveling trends in temple ethnomathematics research and the evolution of the mathematical landscape - Fuat, Fuat; Rohibni, Rohibni; Rayungsari, Maya (Indonesian Journal of Science and Mathematics Education, 2024)
Ethnomathematics has experienced rapid development recently and has become a trend in mathematics. This research uses a systematic literature review method to analyze the relationship between mathematics and culture, trends in mathematical findings, and conformity with ethnomathematics theory. The articles from Sinta's accredited journals over the last five years. The research results show that there is no practical connection between mathematical and cultural concepts in temple ethnomathematics research. Second, mathematical findings tend to be convergent, with most studies referring to the same material without uniqueness or novelty across cultures. Third, Indonesia's natural diversity is not always relevant in ethnomathematics, which focuses more on cultural aspects. In conclusion, there is a gap in ethnomathematics research, and it is suggested that further studies utilize Mathematical Landscape in addressing mathematics in various broader aspects of life that are not directly related to ethnomathematics. This research can serve as a foundation and be further developed to benefit society and education worldwide.